Description of immature stages of Ectemnostega (Ectemnostega) quadrata (Signoret 1885) (Heteroptera: Corixidae), with notes on ecological requirements of the species - Scheibler, Erica Elizabeth (2010)
The family Corixidae comprises a small group of true bugs that live in aquatic environments with abundant macrophytes. The genus Ectemnostega Enderlein includes two subgenera: Ectemnostega and Ectemnostegella, both known from South America, ranging from Ecuador to Tierra del Fuego. Ectemnostega (Ectemnostega) quadrata (Signoret, 1885) is distinguished by the widened posterior half of hemelytra, and the protibia of males prolonged over the base of pala. This species is distributed in Argentina and Chile along the Andes mountain range, from high altitudes in San Juan to sea level in Cabo Hornos, Tierra del Fuego. Adults and larvae were collected in association with Cladophora sp. and Chara sp. in northwestern Mendoza, from Los Horcones Lagoon (2891 m a.s.l.) and from ponds on southwestern slopes of Mendoza (Las Loicas locality, 1772 m a.s.l.). Larval stadia of Ectemnostega are described for the first time. Distributional and life habitats data of this species are provided.